OPTIMIZING DEFINED BENEFIT PENSION PLAN FUNDING: COMBINING ENTRY AGE NORMAL METHOD AND SINGLE SALARY APPROACH - Ekasasmita, Wahyuni; Rahmi, Nur; Tunnisa, Khaera; Amal, Muhammad Ikhlashul (PATTIMURA UNIVERSITY, 2025)
The sustainability of defined benefit pension plans relies heavily on effective funding strategies. This study aims to develop an optimized funding strategy for Defined Benefit Pension Plans by integrating the Entry Age Normal (EAN) method with the Single Salary Approach (SSA). The Entry Age Normal method provides a systematic way to distribute the cost of pension benefits over the career of employees, ensuring long-term stability. Meanwhile, the Single Salary Approach simplifies salary projections, making it easier to manage fund contributions while accounting for future wage inflation. To evaluate the effectiveness of this integrated approach, we conducted a case study using salary and pension fund data collected from internal records at Institut Teknologi Bacharuddin Jusuf Habibie (ITH), a higher education institution. Through a series of simulations and sensitivity analyses, we demonstrate that integrating these methods not only minimizes funding volatility but also improves the accuracy of pension liabilities estimation. For instance, at age 25.83, the actuarial liability is Rp 38,929,501, reflecting a relatively low liability at a younger age. As employees approach retirement, the liability increases significantly. At age 47.17, the liability reaches Rp 191,823,284, demonstrating the impact of salary growth and length of service on future benefits. Additionally, for the same age of 25.83, the actuarial liability under SSA-EAN is Rp 37,980,001, which is slightly lower than the EAN estimate. Pension benefits projected under SSA-EAN are also slightly lower than those under EAN, indicating potential cost savings. The findings provide a viable framework for pension plan administrators seeking to achieve both financial sustainability and predictability in managing pension obligations. By integrating SSA with EAN, this study offers a practical solution that addresses key challenges in the actuarial valuation of defined benefit plans, ensuring more stable and predictable pension funding.